2009
DOI: 10.4103/0019-5278.50716
|View full text |Cite
|
Sign up to set email alerts
|

The exposure to and health effects of antimony

Abstract: Context:This minireview describes the health effects of antimony exposure in the workplace and the environment.Aim:To collate information on the consequences of occupational and environmental exposure to antimony on physiological function and well-being.Methods:The criteria used in the current minireview for selecting articles were adopted from proposed criteria in The International Classification of Functioning, Disability and Health. Articles were classified from an acute and chronic exposure and toxicity th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
69
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(70 citation statements)
references
References 43 publications
0
69
0
1
Order By: Relevance
“…Like many other metals and metalloids, Sb at elevated concentrations may be toxic and potentially carcinogenic (Rossi et al 1987;Cooper and Harrison 2009). It was reported that a significant amount of antimony sulfide (Sb 2 S 3 ) contained in the brake pads is oxidized during braking processes (Von Uexküll et al 2005), thus leading to the formation of the suspected human carcinogen antimony oxide (Sb 2 O 3 ).…”
Section: Introductionmentioning
confidence: 99%
“…Like many other metals and metalloids, Sb at elevated concentrations may be toxic and potentially carcinogenic (Rossi et al 1987;Cooper and Harrison 2009). It was reported that a significant amount of antimony sulfide (Sb 2 S 3 ) contained in the brake pads is oxidized during braking processes (Von Uexküll et al 2005), thus leading to the formation of the suspected human carcinogen antimony oxide (Sb 2 O 3 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, the use of antimony is increasing as a fire retardant in rubber, plastics, pigments, adhesives, textiles and paper; as a fining agent in glass manufacture; and has a long history of use as a medicine in the treatment of parasitic diseases (Sundar and Chakravarty 2010). Leaching antimony from polyvinylchloride (PVC) is enhanced at both low and high pH, by elevated temperature and by contact with body fluids (Cooper and Harrison 2009). Furthermore, recent findings prove that antimony used as polyester catalyst may leach from plastic polyethylene terephthalate (PET) bottles widely used for packaging drinking water or other beverages (Westerhoff et al 2008;Fan et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, urine antimony concentrations in SIDS infants were found to be similar to control and healthy infants, refuting this theory [85]. Detection of antimony in hair of healthy babies further suggested no link between antimony and SIDS [41].…”
Section: Stibinementioning
confidence: 60%
“…Acute ingestion of antimony salts primarily affects the gastrointestinal tract. Toxicity manifests as nausea, vomiting, watery diarrhea, abdominal pain, melena, and hematemesis and may lead to volume depletion and hypovolemic shock [41]. One or two grains of tartar emetic were sufficient to cause death in a child and adult, respectively [44].…”
Section: Clinical Presentation and Lifethreatening Complicationsmentioning
confidence: 99%